Neuroprotective effects of inhaled ferulago angulata oil on scopolamine-induced dementia via anti-oxidative activities in rats - Akbaba, Emel Aydın; Bağcı, Eyüp; Hritcu, Lucian; Mihasan, Marius (My University, 2015)
Ferulago angulata (Apiaceae) is a shrub indigenous to Turkey, western Iran, and Iraq. In traditional medicine, F. angulata is recommended for treating various medical conditions and as sedative. In the study, the effects of inhaled F. angulata essential oil (1% and 3%, daily, 21 days) on spatial memory performance were assessed in scopolamine-treated rats. Decrease of spontaneous alternations percentage within the Y-maze task and increase of working memory errors and reference memory errors within the radial arm maze task were exhibited on scopolamine-induced rats. Exposure to F. angulata essential oil significantly improved these parameters, suggesting positive effects on spatial memory formation. Assessments of oxidative stress markers in the hippocampal tissue of scopolamine-treated rats showed a significant decrease of the total content of reduced glutathione (GSH), superoxide dismutase (SOD), catalase and glutathione peroxidase (GPX) specific activities, along with an increase of acetylcholinesterase (AChE) activity and an elevation of malondialdehyde (MDA) and protein carbonyl levels. F. angulata essential oil significantly increased total content of reduced GSH, SOD, CAT and GPX specific activities, decreased AChE specific activity and attenuated the increased MDA and protein carbonyl levels. Also, DNA fragmantation was not observed in the F. angulata essential oil treated-rats, thus suggesting antiapoptotic activity of the essential oil. Therefore, our results suggest that exposure to F. angulata essential oil ameliorates scopolamine-induced spatial memory impairment by attenuation of the oxidative stress in rat hippocampus.
Bildiri - Yayımlanmış
Keywords: Ferulago angulata essential oil; Spatial memory; Oxidative stress; Alzheimer’s disease